2006
DOI: 10.1002/hep.21100
|View full text |Cite
|
Sign up to set email alerts
|

Interferon α‐2b with and without ribavirin in the treatment of hepatitis B e antigen–positive chronic hepatitis B

Abstract: To study whether interferon (IFN) ␣ and ribavirin combination therapy has a beneficial effect for hepatitis B e antigen (HBeAg)-positive chronic hepatitis B, we enrolled 119 such patients in a randomized study. Fifty-nine patients received 5 million units of IFN-␣2b daily for 4 weeks followed by 5 million units three times a week for 28 weeks, plus 1,200 mg ribavirin daily. Sixty patients received the same dosage of IFN plus placebo. They were followed up for 24 weeks posttreatment, and 105 patients (88%) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…However, these studies, on the association of HBV genotype with response to standard interferon were limited by small sample sizes and retrospective study design. Our recent randomized study on 119 HBeAg-positive patients also showed that genotype B patients have a better sustained HBeAg seroconversion rate to 32 weeks of standard IFN-based therapy than genotype C patients (44% vs. 22%, P = 0.02) [109]. The relationship between viral genotype and response to pegylated interferon is similar to that observed with standard interferon.…”
Section: Genotypessupporting
confidence: 59%
“…However, these studies, on the association of HBV genotype with response to standard interferon were limited by small sample sizes and retrospective study design. Our recent randomized study on 119 HBeAg-positive patients also showed that genotype B patients have a better sustained HBeAg seroconversion rate to 32 weeks of standard IFN-based therapy than genotype C patients (44% vs. 22%, P = 0.02) [109]. The relationship between viral genotype and response to pegylated interferon is similar to that observed with standard interferon.…”
Section: Genotypessupporting
confidence: 59%
“…In a subsequent large randomized trial, consistent findings were noted [18]. A total of 119 HBeAg-positive patients received 5 MU of IFN-2b daily for 4 weeks followed by 5 MU three times weekly for 28 weeks.…”
Section: Influence Of Hbv Genotype On Interferon Therapysupporting
confidence: 53%
“…PEG-IFN -2b is effective against HBeAg-positive CHB, but combinations with lamivudine [94] or ribavirin [95] gave no additional benefit. In contrast, a recent combination treatment study in CHB patients by Wursthorn et al using PEG-IFN -2b and adefovir showed a strong reduction in HBV DNA, cccDNA and HBsAg levels [96].…”
Section: Plough) and Pegylated Interferon -2a (Peg-ifn;mentioning
confidence: 97%